NEW APPROACH OF TPA BASED DATA ACCESS MODEL - Bhardwaj, Ashish,; Yadav, Surendra, (International Journal of Psychosocial Rehabilitation, 2020)
Data access and storage are the basic needs for any organization, and they are a part of any organization's routine activity. When performing data access, the main concern is regarding the ease of access to and transfer of data with the proper security for that data. Data access distinguishes the roles and responsibilities between the abilities of administrators & that of end users while accessing the repository or the stored data. This paper presents a TPA-based security model that performs data sharing through encrypted data chunks. This model is not only effective in terms of the data transfers but also more secure than the existing models.